Francischanos, a replacement genus for Dastilbe moraesi Silva-Santos, 1955, from the Quiricó Formation, Lower Cretaceous of the Sanfranciscana basin, Brazil (Ostariophysi: Gonorynchiformes) - Ribeiro, Alexandre C.; Bockmann, Flávio A.; Poyato-Ariza, Francisco J. (Cretaceous research, 2022)
Francischanos gen. nov. is erected herein as a replacement genus for Dastilbe moraesi Silva-Santos, 1955. The gonorynchiform chanid Dastilbe and its species arrangement have been a matter of debate for decades. Recent phylogenetic revision with a new cladistic analysis has shown that Dastilbe moraesi is a valid species, yet quite distinct from other species of the genus. A new anatomic description of this species is provided, confirming that Francischanos gen. nov. moraesi is distinguished from all other species of chanids by the autopomorphic presence of only five hypurals in the caudal endoskeleton plus a unique combination of characters, including the morphology of: the posterior border of the exoccipitals and their expansions above the supraoccipital; the anterior maxillary process; the symphysis formed by the dentaries; and the preopercular bone. The new taxon is more closely related to the living Chanos chanos than to any valid species of Dastilbe. With this new genus, the number of chanid genera described from the Lower Cretaceous of Brazil increases to four, an unusual diversity for this scarce group. urn:lsid:zoobank.org:pub:B0805807-9CCF-46FC-9966-E589850D0012 •Francischanos gen. nov. is erected as a replacement genus for Dastilbe moraesi Silva-Santos, 1955 from Sanfranciscana basin (lower Aptian).•Analysis was based on type specimens as well as additional material from type-locality.•Our findings indicated that fossil gonorynchiforms previously assigned to Dastilbe crandalli can represent a species complex.